Keberlanjutan Kampung Lama Berbasis Potensi Kearifan Lokal di Kota Semarang - Annisa Mu'awanah Sukmawati (Universitas Islam Negeri Sunan Ampel Surabaya, 2017)
The old kampung is an embryo of urban development which has historical and cultural values, as well as the identity. However, the old kampung is threatened physically and noThe old kampung was an embryo for urban development which has historical and cultural values, as well as the identity. However, the old kampung was threatened physically and non-physically due to urban development. The article aimed to showed the strategies to achieve kampung sustainability through the potential of local wisdom. A qualitative research method conducted with qualitative descriptive analysis technique by taking Kampung Bustaman, Semarang as the study location. The analysis showed that Kampung Bustaman has local wisdom in the form of economic activities that has been manifested in the community daily lifes and potentially became the major capital to achieve kampung sustainability. The strategies involved the stakeholder roles, such as local communities, government and other parties through the kampung events. The tourism was able to encouraged communities participation and strengthen the economic as well as the social life of local communities. Local communities participation and local organizations commitment to preserving local wisdom also play an important role for achieving the kampung sustainability.nphysically due to urban development. The article aims to show the strategy to achieve kampung sustainability through the potential of local wisdom. The study was conducted by using qualitative research method with qualitative descriptive analysis technique by taking the study area in Kampung Bustaman, Semarang City. The analysis shows that Kampung Bustaman has local wisdom in the form of economic activity that has been manifested in the daily life of the community and potentially as the capital to achieve kampung sustainability. The strategy to achieve kampung sustainability involves the role of stakeholders, such as local communities, government and other parties through the kampung events. The tourism is able to encourage the communities participation and strengthen the economic and social life of local community. Local community participation and local organizations' commitment to preserving local wisdom also play an important role in achieving kampung sustainability.